2014
DOI: 10.1371/journal.pone.0106131
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Reveals Epithelial Mesenchymal Transition (EMT) Genes Can Selectively Differentiate Eribulin Sensitive Breast Cancer Cells

Abstract: ObjectivesEribulin mesylate is a synthetic macrocyclic ketone analog of the marine sponge natural product halichondrin B. Eribulin is a mechanistically unique inhibitor of microtubule dynamics In this study, we investigated whether selective signal pathways were associated with eribulin activity compared to paclitaxel, which stabilizes microtubules, based on gene expression profiling of cell line panels of breast, endometrial, and ovarian cancer in vitro.ResultsWe determined the sets of genes that were differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 38 publications
7
49
0
2
Order By: Relevance
“…Genetic mutation of the chromatin remodelling complex has been identified as a mechanism of tumour occurrence and development . Here, we analyse the transcriptional profiling of paclitaxel‐sensitive DU4475 and paclitaxel‐resistant MDA‐MB436 without or with paclitaxel treatment, which was determined previously . We found that the AT‐rich interaction domain 1A (ARID1A) is up‐regulated in DU4475 cells but is down‐regulated in MDA‐MB436 cells.…”
Section: Introductionmentioning
confidence: 83%
“…Genetic mutation of the chromatin remodelling complex has been identified as a mechanism of tumour occurrence and development . Here, we analyse the transcriptional profiling of paclitaxel‐sensitive DU4475 and paclitaxel‐resistant MDA‐MB436 without or with paclitaxel treatment, which was determined previously . We found that the AT‐rich interaction domain 1A (ARID1A) is up‐regulated in DU4475 cells but is down‐regulated in MDA‐MB436 cells.…”
Section: Introductionmentioning
confidence: 83%
“…EMT is a process in which epithelial cells acquire mesenchymal properties and show loss of intercellular cohesion, increased cellular migration, and increased resistance to anticancer agents. Importantly, the EMT signature correlates with eribulin resistance in breast cancer cells in vitro (29), cisplatin resistance in ovarian cancer (30,31), and resistance to gemcitabine, 5-FU and cisplatin in pancreatic cancer (32). Our previous study demonstrated that the EMT-associated genes N-cadherin , vimentin and Snail were upregulated in HOC313 cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…A reason for this result might be that HT-29 IEC already have a distinct epithelial phenotype more similar to a physiologically configured epithelium, while TNBC seems to have a more stem-cell like mesenchymal behavior corresponding to the cells of an aggressively metastatic type of cancer. It has already been shown that the expression of some EMT marker genes predicts Eribulin sensitivity in some cell lines [24]. Interestingly, Eribulin not only enhanced the mRNA expression of the EMT markers SLUG and vimentin but also promoted E-cadherin expression, a marker associated with an epithelial phenotype.…”
Section: Discussionmentioning
confidence: 87%
“…After 12 h, the medium was replaced by low-glucose DMEM without additives. After 8 h, the medium was replaced by low-glucose DMEM with 0.1, 0.5, 1, 5, 50, 100, or 500 ng/mL Eribulin as indicated and stimulated for 4,8,24,48, and 72 h. Cell supernatant was used to perform an LDH assay (Sigma-Aldrich, St. Louis, Missouri, USA), which quantifies LDH released after cell damage. Cell Counting Kit-8 (CCK8; Dojindo Molecular Technologies, Rockville, Maryland, USA) was used to evaluate cell proliferation and cytotoxicity.…”
Section: Cell Viability Assaymentioning
confidence: 99%